PERANGKAT LUNAK TATA KELOLA DESA BERBASIS SMS GATE WAY PADA DESA SUKARENDAH - Hendra, Yul; Fatullah, Rizki (Jurnal Ilmiah Sains dan Teknologi, 2018)
This research designs and makes a software that helps village officials in managing the village data such as data processing of domicile certificate, move and business license. With this application allows information to be conveyed to the village community can be more quickly received through the SMS Gateway feature. Villagers are also easy to see the status of the various letters that have been done, because it can be monitored online. With this software villagers can download information about the village, the various requirements for mail processing as well as other important information. When there is information to be conveyed quickly to masyarakatpun can be delivered quickly through the SMS Gateway feature because the average villager now has a handphone.Perangkat is developed using Waterfall method